2021
DOI: 10.3389/fpls.2021.687826
|View full text |Cite
|
Sign up to set email alerts
|

RNA N6-Methyladenosine Responds to Low-Temperature Stress in Tomato Anthers

Abstract: Cold stress is a serious threat to subtropical crop pollen development and induces yield decline. N6-methyladenosine (m6A) is the most frequent mRNA modification and plays multiple physiological functions in plant development. However, whether m6A regulates pollen development is unclear, and its putative role in cold stress response remains unknown. Here, we observed that moderate low-temperature (MLT) stress induced pollen abortion in tomato. This phenotype was caused by disruption of tapetum development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Therefore, the mechanism underlying the regulatory effect of m 6 A modification on mRNAs under solar-withering stage needs in-depth dissection. A recent study unveiled that abiotic stress leads to the relocation of m 6 A enrichment on mRNA transcripts [9]. Data from this study showed that m 6 A peaks in CsDXS and other three DMP-associated genes were all distributed within 3′UTR and around stop codon under solar-withering, indicating that solar-withering only affects m 6 A levels of these DMP-associated genes but did not redistribute m 6 A marks on these genes.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, the mechanism underlying the regulatory effect of m 6 A modification on mRNAs under solar-withering stage needs in-depth dissection. A recent study unveiled that abiotic stress leads to the relocation of m 6 A enrichment on mRNA transcripts [9]. Data from this study showed that m 6 A peaks in CsDXS and other three DMP-associated genes were all distributed within 3′UTR and around stop codon under solar-withering, indicating that solar-withering only affects m 6 A levels of these DMP-associated genes but did not redistribute m 6 A marks on these genes.…”
Section: Discussionmentioning
confidence: 71%
“…Evidence is accumulating that m 6 A deposition affect the mRNA levels under different developmental stages or environmental stresses [9,13,32,35]. To evaluate the overall correlation between m 6 A modification and gene expression levels under solar-withering, a total of 1137 DMP-associated genes with altered expression levels between samples were selected (Figure S5).…”
Section: Analysis Of Dmp-associated Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the m 6 A-mediated stress responses have been extensively studied in ª 2022 The Authors. Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd., 20, 1447-1455 various crops, including tobacco (Nicotiana tabacum) (Li et al, 2018), rice (Cheng et al, 2021;Shi et al, 2019b;Tian et al, 2021;Zhang et al, 2021a), wheat (Sun et al, 2020;Zhang et al, 2021b), sweet sorghum (Zheng et al, 2021), tomato (Yang et al, 2021), apple (Guo et al, 2021;Mao et al, 2021), and pakchoi (Liu et al, 2020).…”
Section: Regulatory Mechanisms Of M 6 a On Crop Stress Responsesmentioning
confidence: 99%
“…In Arabidopsis, thousands of transcripts contain m 6 A modifications, which distribute preferentially around the stop codon or in the 3′ untranslated region (UTR) (Luo et al ., 2014 ; Wan et al ., 2015 ). This distribution preference is conserved among several important crops, including rice ( Oryza sativa ) (Cheng et al ., 2021 ; Zhang et al ., 2019a ), maize ( Zea mays ) (Miao et al ., 2020 ), wheat ( Triticum aestivum ) (Zhang et al ., 2021b ), tomato ( Solanum lycopersicum ) (Hu et al ., 2021b ; Yang et al ., 2021 ; Zhou et al ., 2019 ), and sweet sorghum ( Sorghum bicolor ) (Zheng et al ., 2021 ) (Figure 1 ). A recent study that compared the m 6 A methylomes for 13 representative plant species spanning over half a billion years of evolution confirmed the conserved distribution of m 6 A modifications in the stop codon and 3′ UTR regions (Miao et al ., 2022 ).…”
Section: A Characteristics In Cropsmentioning
confidence: 99%